Adventure-based education: a quantitative evaluation of the impact of program participation in high school on youth development - Palmer, Sally Owens, author; Anderson, Sharon, advisor; Gloeckner, Gene, committee member; MacPhee, David, committee member; Frederiksen, Heidi, committee member (Colorado State University. Libraries, 2015)
Adventure-based physical-education (ABPE) classes have become a more prevalent class offering in many middle and high schools throughout the United States. Several studies have researched the outcomes and benefits of adventure-based programs (e.g., Cason & Gillis, 1994; Gillis & Speelman, 2008; Hans, 2000; Hattie, Marsh, Neill, & Richards, 1997), and links have been made between youth-development constructs and adventure programming (e.g., Henderson, Powell, & Scanlin, 2005; Sibthorp & Morgan, 2011). To date, limited research has focused on the progression of positive-youth development (PYD) constructs in high-school students participating in a semester-long ABPE course. This research study examined the progression of PYD of students throughout the course of a semester who were enrolled in an ABPE class compared to that progress for those who were not enrolled in any adventure classes at all. Results suggested that there were no significant differences in PYD throughout the semester for students who were enrolled in adventure classes compared to the PYD of those students who were not in any adventure classes at all. There were, however, significant differences in connection for students who were in the Adventure Leader class compared to connection for those who were not in any adventure classes at all. The findings of this research study highlight the need for more studies that examine different types of adventure classes or activities, as opposed to adventure classes or activities as a whole.
Keywords: five cs; human development; youth development; high school; adventure education; ropes course